An effective real-time flood disaster management with automated GSM warning system - Faruk, Omar; Aliva, N Afrida Nawar; Salmani, Md. Golam; Islam, Raisa (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.